P220 Urinary incontinence in chronic cough. (12th November 2019) - Cho, PSP; Dicpinigaitis, PV; Fletcher, HV; Turner, RD; Birring, SS
Abstract : Introduction: Cough leads to increased intra-abdominal pressure, thus chronic cough may increase the risk of stress urinary incontinence. We investigated the prevalence, duration and frequency of urinary incontinence in female patients with chronic cough. Methods: Consecutive female patients with chronic cough were recruited from a tertiary specialist cough clinic. Participants self-completed a structured questionnaire to record demographics, anthropometrics, duration of cough, and presence, duration and frequency of urinary incontinence. Results: 71 participants; mean (SD) age 57.0 (14.0) years, median (IQR) BMI 26.9 (23.1–33.4) kg·m -2 and duration of cough 6 (3–15) years; were recruited. 40 (56%) participants reported urinary incontinence; median (IQR) duration 4.0 (3.0–6.5) years. The frequency of urinary incontinence episodes was daily, 1–6 times weekly and less than once a week in 18 (45%), 8 (20%) and 12 (30%) patients respectively. 28 of 40 (70%) participants reported that urinary incontinence only occurred after coughing, thus had stress incontinence. 18 of 40 (45%) participants reported their onset of urinary incontinence followed the onset of chronic cough. There was no significant difference in age (p=0.742), BMI (p=0.907) and duration of cough (p=0.964) between patients with and without urinary incontinence. Discussion: Urinary incontinence affects over half of female patients with chronic cough. Further studies should investigate the characteristics of urinary incontinence in a larger population (stress vs irritable bladder). There is also a pressing need to develop clinical management protocols for cough related incontinence.